2021
DOI: 10.1109/access.2021.3081566
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Generation and Application of a Bandwidth Multiplied Linearly Chirped Signal With Phase Modulation Capability

Abstract: Photonic generation of a bandwidth multiplied linearly chirped signal with phase modulation capability is proposed and its applications in communication and radar systems are demonstrated. In the generator, a dual-polarization quadrature phase shift keying modulator is used to simultaneously perform bandwidth multiplication and phase modulation. The generator can be functionally expanded to a transceiver for wireless communication, which can be used to perform optical generation and coherent demodulation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Previously, Nie et al demonstrated a photonic system by superposing amplitude shift keying (ASK) modulation to a linear frequency modulation (LFM) signal by simply adding a Mach-Zehnder Modulator (MZM) to a photonic radar system [10]. Li et al proposed a similar optical system by using linear frequency modulation and phase shift keying (LFM-PSK) for sensing and communication [11]. It has been demonstrated that microwave photonic systems possess a wide bandwidth to uphold a high data rate [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Nie et al demonstrated a photonic system by superposing amplitude shift keying (ASK) modulation to a linear frequency modulation (LFM) signal by simply adding a Mach-Zehnder Modulator (MZM) to a photonic radar system [10]. Li et al proposed a similar optical system by using linear frequency modulation and phase shift keying (LFM-PSK) for sensing and communication [11]. It has been demonstrated that microwave photonic systems possess a wide bandwidth to uphold a high data rate [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many schemes of photonic-aid LFM-based shared waveform generation has been proposed over the past pentad [7][8][9][10][11][12][13][14][15][16]. In 2019, an amplitude shift keying (ASK)-LFM waveform with a 4 GHz bandwidth and a data rate of 100 Mbps was realized via photonic approach for the first time [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, these schemes employed inter-pulse coding, resulting in a low bit rate dictated by the pulse repetitive frequency (PRF) of radar. On the other hand, numerous efforts on photonic generation of PSK-LFM waveforms have been made [9][10][11][12][13][14][15]. By employing inner-pulse modulation, variable phase deviation, pseudo-random coding, and phase compensation, the mutual interference between sensing and communication functions was significantly mitigated, leading to enhanced overall performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complexity of the OEO and the limited oscillating modes hinder the precision of the generated LFM signal. Recently, we proposed a frequency multiplied phase-coded LFM signal generator based on a DPol-DPMZM [28] . Bandwidth doubled or quadrupled LFM waveform can be obtained and be used for radar detection and covert communication.…”
Section: Introductionmentioning
confidence: 99%